Location of caoutchouc in teak. - H Simatupang, Maruli
Teak is one of the most valuable wood species in the world, and is currently cultivated in many parts of the world (Premrasmi and Dietrichs 1967, Dahms 1989). The wood has outstanding properties in durability (Da Costa et al. 1958, Sandermann and Simatupang 1966, Findlay 1985), iron stains (Ser and Neo 1982), and dimensional stability (Choong and Achmadi 1991).